An Automated Local Binary Pattern Ship Identification Method by Using Sound - Tuncer, Türker; Aydemir, Emrah (My University, 2020)
Sound classification is one of the most important areas of research for mechanics and applied computersciences. Using the sound classification method, many biometric applications/methods have been presented inthe literature. This study presents a ship identification method using sounds. The method presented here isvery simple and effective. It has only two fundamental phases and these are feature extraction by onedimensional binary pattern (1D-BP) and classification with conventional classifiers phases. 1D-BP extracts256 features from each sound and these sounds are forwarded to classifiers. To test this ultra-lightweightsound identification method, a ship sounds dataset was collected from YouTube. According to our results, thismethod achieved a 97% classification accuracy. This result clearly demonstrates the merits of the 1D-BP basedon ship sound classification method and the sound-based ship identification method which we present here.
Keywords: Mühendislik; Deniz; Bilgisayar Bilimleri; Yazılım Mühendisliği; Bilgisayar Bilimleri; Donanım ve Mimari